Psychologiczne następstwa niedowidzenia - Łazarczyk-Kirejczyk, Joanna; Szulc, Agata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
This is the review of references about problem of amblyopia and its psychosocial effects on children being cured. The study emphasies the need for psychological approach to problems that trouble children wearing glasses, suffering from strabismus and being cured by occlusion.